PENERAPAN TEKNIK FADING PADA ANAK DENGAN PERILAKU AGRESIF - Merlin Gani (Irfani, 2018)
Aggressive behavior is deviant and negative that we often encounter in children aged 2, 3 to 5 years. This attitude often causes the child isolated from her friends as well as dangerous to others what if this behavior had to be hurt or attacked physically. The factors that cause children to be in an aggressive manner that is caused by internal factors or derived from the child itself and eksteren factors derived from family, school, friends and the community around it. It's necessary to get special attention for an educator (teacher) who berlaporan guiding children toward positive. Therefore, this aggressive behavior can be reduced or minimized by using means, methods, techniques, or a particular approach. One of them uses teknih Fading which is a technique of gradually changing the behavior of the smallest things such as giving praise to the stage to give rewards or gifts to the children who were able to show good behavior.